A urinary peptidomic profile predicts outcome in SARS-CoV-2-infected patients - Wendt, Ralph; Thijs, Lutgarde; Kalbitz, Sven; Mischak, Harald; Siwy, Justyna; Raad, Julia; Metzger, Jochen; Neuhaus, Barbara; Leyen, Heiko von der; Dudoignon, Emmanuel; Mebazaa, Alexandre; Spasovski, Goce; et al. (Elsevier BV, 2021)
COVID-19 prediction models based on clinical characteristics, routine biochemistry and imaging, have been developed, but little is known on proteomic markers reflecting the molecular pathophysiology of disease progression.